Penggunaan Media Berbasis Game Edukasi Quizizz Untuk Menumbuhkan Nilai Kejujuran Siswa Pada Pembelajaran Daring - Neva Kurnia Faini; Alexon Alexon; Pebrian Tarmizi (Universitas Bengkulu, 2021)
This study aimed to foster the value of honesty of grade VA students at Elementary School 81 Bengkulu City by using the Quizizz game media. This research is a Classroom Action Research (CAR). The subjects of this study were teacher and 18 students consist of 11 male students and 7 female students. The research procedure is in the form of a cycle. Each cycle consists of four stages including: planning, implementing, observing and reflecting. The research instrument was in the form of a Quizizz game media observation sheet and a student honesty value questionnaire. The data analysis techniques were used: the observation sheet using the formula of the average score, the highest score, the lowest score, the difference in scores and the range of values for each criterion and quantitative descriptive analysis. Based on the result of the study it was concluded that (1) the existence of educational game-based media Quizizz provides an alternative to online learning in schools; (2) the use of Quizizz educational game-based media can foster the honesty value of fifth grade students of Elementary School 81 Bengkulu City in online learning.